Rodzina von Leslav i jej działalność w XIV-XV wieku = The family von Leslav in XIV-XV C. - Karczewska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the genealogy, origins, history and estates of the knightly family von Leslav. Their main estates were located around Zielona Góra and the family seat was Leśniów Wielki. Over the period of XIV-XV, members of the family von Leslav made secular and clerical careers in the court of Duke of Głogów and in religious establishments on the territory of the duchy of Głogów. They acquired high social status and played an important role in their communities, serving the local Piast dynasty.
Keywords: Zielona Góra (okręg) - historia; Leśniów Wielki - historia; Księstwo Głogowskie - 14-15 w.; Leslav von (ród); 14-15 w.